Perbedaan Pengaruh Latihan Menggiring Bola Menggunakan Model Variasi Dan Pengaruh Latihan Reguler Terhadap Teknik Menggiring Bola pada Anak Latih Sekolah Sepak Bola Pabrik Gula Ngadirejo Kediri Usia 14 Tahun - Sandhi, Dionika Tikta; Budiwanto, Setyo (Performance, 2017)
Abstract: The aimed of this study was to determine the effect of dribbling exercise of model variation and the effect of regular exercise on dribbling skills in children practiced of Ngadirejo Sugar Factory Soccer School, Kediri in the age of 14 years. The study designs which used is an experiment conducted to train the trained children of Football School in Ngadirejo Kediri Sugar Factory with an age range of 14 years. A number of samples are 60 trained children  and divided into two groups with ordinal pairing matching techniques. Instruments used in the research is to test the dribble. Thirdly, is a significant difference between the dribble using a variational model with regular exercise against the trained children's dribbling skills in Football School Ngadirejo Sugar Factory, Kediri (t = -4.3667> t table 2.000). Suggestion can be given to the coach of School Football in Sugar Factory Ngadirejo Kediri, preferably using a using variational model of dribbling  as a form of exercise to improve the skills of dribbling, due to the result of the research that has been done is  explained that using variational model of dribbling gives a better effect than the regular practice of the dribbling skills for trained children in Football School of Ngadirejo Sugar Factory, Kediri in the age of 14 Years old.Keywords:    the variational model of dribbling exercise in football, regular exercise, soccer dribbling skills techniquesAbstrak: Penelitian ini bertujuan untuk mengetahui pengaruh latihan menggiring bola menggunakan model variasi dan pengaruh latihan reguler terhadap keterampilan menggiring bola pada anak latih Sekolah Sepakbola Pabrik Gula Ngadirejo Kediri usia 14 tahun. Rancangan penelitian yang dipakai adalah eksperimen yang dilakukan kepada anak latih Sekolah Sepakbola Pabrik Gula Ngadirejo Kediri dengan rentang usia 14 tahun. Jumlah sampel 60 anak latih dan dibagi dalam dua kelompok dengan teknik ordinal pairing matching. Dari hasil penelitian yang telah dilakukan ternyata latihan mengggiring bola menggunakan model variasi memberikan pengaruh yang lebih baik dari pada latihan reguler terhadap keterampilan menggiring bola. sebaiknya menggunakan latihan menggiring bola menggunakan model variasi sebagai bentuk latihan untuk meningkatkan keterampilan menggiring bola pada latih Sekolah Sepakbola Pabrik Gula Ngadirejo Kediri (t hitung = -4,3667 > t tabel 2,000).Kata kunci: latihan variasi menggiring bola, latihan reguler, teknik menggiring bola